Low-Cost CCTV for Home Security With Face Detection Base on IoT - Pane, Muhammad Akbar Syahbana; Saleh, Khairul; Prayogi, Andi; Dian, Rahmad; Siregar, Ratu Mutiara; Aris Sugianto, Raden (Journal of Information Systems and Technology Research, 2024)
Monitoring is a necessary part of Home surveillance that can be done through the internet network as a security measure. Many CCTV cameras on the market today continue to employ analog and conventional technology, specifically coaxial wire. As a result, extra expenditures for CCTV system wiring are required; besides being more expensive, the installation takes more handling, as the picture data cable and control signal cable cannot be merged. This project aims to develop a security system capable of detecting object movement in real-time utilizing a webcam camera attached to a raspberry pi. The findings of this study enable the development of a low-cost CCTV system that can be monitored remotely via the Internet of Things.